Peningkatan Efisiensi Monitoring Status Gizi Anak melalui Pembangunan dan Pendampingan Penggunaan Sistem Informasi untuk Kader Posyandu: Increasing the Efficiency of Monitoring Children's Nutritional Status through Development and Assistance in the Use of Information Systems for Posyandu Cadres - Yusuf, Mukarramah; Ilham, Amil Ahmad; Paundu, Ady Wahyudi; Warni, Elly; Batara U, A Sungkurawira; Chudori, Paula C; Yusri, Amiqatun Nasyati; Saadputra, Zulfiqry (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Posyandu volunteers (cadre) have an essential role in the early detection of stunting in children under two years, achieved through routine weighing and monitoring of children's growth. This community service activity helps Posyandu volunteers in their role of recording and reporting. Posyandu volunteers use the SIP Book (Posyandu Information System) to record and report the results of activities at Posyandu and monitor maternal and child health, including children's nutritional status. Manually recording the nutritional status of children registered in Posyandu by the volunteers creates time inefficiencies in organizing the Posyandu. For this reason, an information system was built to precisely meet the needs of Posyandu volunteers in their role to monitor stunting in their work area. This information system is website-based and manages nutritional status data for toddlers at Posyandu. This system was tested on Posyandu volunteers in Nisombalia village, Maros Regency, South Sulawesi. Evaluation through questionnaire shows an improvement (from bad to very good) in terms of ease of recording and monitoring the nutritional status of children registered with Posyandu.